Multilingual development - a longitudinal study - Gogolin, Ingrid; Klinger, Throsten; Schnoor, Birger; Usanova, Irina (Revista de Investigación Educativa, 2021)
Does multilingual development bolster or obstruct educational success? This was the starting question for the research project “Multilingual Development - a Longitudinal Perspective” that will be presented here. While multilingualism has often been cited as a disadvantage, there are also indications that it supports successful (language) learning. It was therefore a goal of the project to obtain primary information on the language development of multilingual secondary school pupils in Germany in order to contribute to the further clarification of this question. The project is based on data of receptive (reading) and productive (writing) language skills in German (the language of schooling), Russian and Turkish as immigrants’ heritage languages, English (the first foreign language taught in primary school already) and for a part of the sample French or Russian (as second foreign languages taught in academic track schools). With this range, it was possible to examine the linguistic profiles of the participants as well as reciprocal influences between languages. The sample included roughly 2000 students, tested at four measurement points in the course of secondary schooling. This is the first interdisciplinary study worldwide which includes the complexity of multilingual development on the basis of a substantial sample of respondents, measured language data a wide range of background data for statistical control of influencing background factors. The project thereby creates new knowledge about the complexity of language development in the context of migration, as well as a new basis for the design of language education in linguistically heterogeneous schools. In this contribution, we focus on one of the premier outcomes of our project: the development of an innovative test for the measurement of multilingual writing skills.